Mimogonellus Fagel and Thoracophorus Motschulsky (Coleoptera: Staphylinidae: Osoriinae) new to Korea - Park, Joon-Yong; Ahn, Kee-Jeong (Journal of Asia-Pacific biodiversity, 2024)
Mimogonellus japonicus (Naomi) and Thoracophorus (Thoracophorus) certatus Sharp are identified for the first time in the Korean peninsula. The genera Mimogonellus Fagel and Thoracophorus Motschulsky are also new records to the Korean fauna. Diagnoses and illustrations of the habitus and diagnostic characters of these two species are provided to facilitate identification.